The story of Tracy Beaker - Wilson, Jacqueline; Sharratt, Nick (London : Corgi Yearling, 2006)
Ten-year-old Tracy, who lives in a children's home because her mother was forced to give her up, dreams of getting a good foster family where she can be happy until her mother comes back for her.
"A Corgi Yearling book.".
"First published in Great Britain by Doubleday Children's Books ... 1991"--T.p. verso.
Keywords: Foster home care -- Fiction; Mothers and daughters -- Fiction; Foster home care -- Fiction; Mother-daughter relationship -- Fiction